HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN PERSALINAN SUNGSANG DI RSUD ULIN BANJARMASIN TAHUN 2013 - Riskiviawinanda, Firdausi; Aditya, Renny; Mutmainnah, Noor (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
Breech delivery is a labor complication which could come to death of fetus. Some risk factors of breech delivery are age and parity. This research had a purpose to know the relation of age and parity with breech delivery at RSUD Ulin Banjarmasin in 2013. This research had used analitic observational metode with cross-sectional approachment. Data analytic which had been used was chi-square test. Result of this research had shown that from 284 research subjects who gave birth at RSUD Ulin Banjarmasin, 89 (31,34%) research subjects had breech delivery and 195 (64,86%) research subjectsÂ had normal labor without complications. There were 72 (29,15%) breech deliveries from all research subjects who had no risk ages. There were 17 (45,95%) breech deliveries from all resarch subjects who had risk ages. There were 38 (25,68%) breech deliveries from all research subjects with primiparity. There were 51 (37,50%) breech deliveries from all research subjects with multiparity. The result of chi- square test for the relationship between age and breech delivery was P=0,040 with POR=2,06) and the relationship between parity and breech delivery was P=0,032 with POR=1,73. So, there was a relitionship of ages and parity in breech delivery at RSUD Ulin Banjarmasin 2013.Â Keywords: breech delivery, age, parity